2008
DOI: 10.1007/s00432-008-0387-1
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the novel serotonin receptor subunit gene HTR3C show different risks for acute chemotherapy-induced vomiting after anthracycline chemotherapy

Abstract: The aim of this study was to correlate chemotherapy-induced nausea and vomiting (CINV) with commonly occurring single nucleotide polymorphisms (SNP) in the 5-hydroxytryptamine receptor 3 genes (HTR3). Women with breast cancer without previous chemotherapy were eligible for this prospective study. All patients received epirubicin, with or without cyclophosphamide, and preventive medication with ondansetron and dexamethasone. The patients documented every vomiting event on an hourly basis. Real-time polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 15 publications
1
67
0
2
Order By: Relevance
“…It has been shown that ondansetron is mainly metabolized by CYP1A2, CYP2D6 and CYP3A4 (15). Finally, other studies suggested that variation of 5-HT3B, 5-HT3C and 5-HTR3D receptors could be the predictors of 5-HT3RAs' efficacy in cancer patients (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ondansetron is mainly metabolized by CYP1A2, CYP2D6 and CYP3A4 (15). Finally, other studies suggested that variation of 5-HT3B, 5-HT3C and 5-HTR3D receptors could be the predictors of 5-HT3RAs' efficacy in cancer patients (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In the present analysis, however, our results of rs6766410 (HTR3C) and rs4680 (COMT) were inconsistent with the previous findings, which CINV occurred in 50% of the patients with C/C homozygosity of rs6766410 (HTR3C), compared to 19% of those with A/A homozygosity and 22% of those with A/C heterozygosity. 8) Further, COMT activity in G/G homozygotes on rs4680 was approximately 3 to 4 times higher than that in A/A homozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of gene polymorphisms such as those in the serotonin 5-HT 3A receptor, 7) 5-HT 3B receptor, 6) 5-HT 3C receptor, 8) cytochrome P-450 2D6, 33) and P-glycoprotein 34) for the purpose of investigating whether genetic factors influence the efficacy of the antiemetic agents used for CINV revealed that certain gene polymorphisms were associated with nausea and vomiting. However, there have been no studies to investigate the association between gene polymorphisms and the efficacy of antiemetic therapies on CINV in Japanese cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fasching et al reported an association of the HTR3C p.163N allele with the occurrence of vomiting in breast cancer patients undergoing chemotherapy (p = 0.009) [16]. In a different study, a homozygous deletion in the promoter region of the HTR3B gene, c.-104_-102del-AGA, present in only 1.2% of 242 patients, involved a higher probability of acute emesis (p = 0.008) [17].…”
mentioning
confidence: 95%